ANALISIS KEBUTUHAN GURU DALAM PEMBENTUKAN KARAKTERISTIK SISWA DENGAN KURIKULUM MERDEKA DI SEKOLAH DASAR NEGERI 98 PEKANBARU (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
This research aims to understand the needs of teachers in shaping student character at SD Negeri 98 Pekanbaru in the context of implementing the Independent Curriculum. Through interviews, observations and documentation, this research found that teachers are committed to creating active and student-centered learning. However, teachers also face challenges in accessing relevant learning resources and keeping up with current developments. This research uses a qualitative descriptive method to obtain an in-depth picture of the needs of teachers in forming student characteristics at SD Negeri 98 Pekanbaru. In conducting research, certain data and data sources are needed that suit the needs or problems to be researched. Data was obtained from teachers at SD Negeri 98 Pekanbaru. Then additional data sources were obtained from articles/journals. Analysis of teachers' needs in building student character with the Merdeka Curriculum at SD Negeri 98 Pekanbaru shows that teachers need special training in character development, support in designing meaningful learning activities, or access to relevant resources.